Case report: Sustained complete remission with all-oral MEPED therapy in a patient with Hodgkin’s disease developing resistance to pembrolizumab - Reuthner, K.; Aubele, P.; Menhart, K.; Rath, P.; Harrer, D. C.; Herr, W.; Hahn, J.; Vogelhuber, M.; Heudobler, D.; Lueke, F.; Reichle, A.; Grube, M. (Frontiers in Pharmacology, 2024)
Targeted chemotherapy and immune checkpoint inhibitors (ICPi) have expanded the spectrum of therapies for patients with relapsed/refractory (r/r) Hodgkin's disease and significantly improved the proportion of patients with long-term disease control. However, there is no standardized therapeutic option in case of further progression. Recently, we demonstrated that therapy with MEPED (metronomic chemotherapy, everolimus, pioglitazone, etoricoxib, dexamethasone) is highly effective in patients with r/r Hodgkin's disease. The benefit after pretreatment with ICPi has not been studied, yet. Here, we report a patient with progressive Hodgkin's disease on Pembrolizumab for the first time who achieved sustained complete remission (CR) after initiation of MEPED therapy. A 57-year-old patient was pre-treated with brentuximab vedotin for relapsed advanced Hodgkin's disease and had received Pembrolizumab for progression from November 2020 to July 2022. Due to further progression, MEPED therapy was started in August 2022 and continued until May 2023. It consisted of a strictly oral daily (28-day cycle) application of lowdose treosulfan 250mg, everolimus 15mg, pioglitazone 45mg, etoricoxib 60mg, and dexamethasone 0.5mg. Treatment response was evaluated by F-18 FDG-PET/CT (PET/CT). CR was defined by a negative Deauville score (DS) of 1-3. Already three months after starting MEPED, a CR (DS: 3) was confirmed by PET/CT in November 2022. The next follow-up in May 2023 continued to show CR (DS:3). The therapy was very well tolerated. No hematological or other organ toxicity was observed. However, in May 2023 the patient presented with leg edema and weight gain, most likely due to pioglitazone and the PET/CT revealed suspected everolimus-induced pneumonitis, so MEPED was discontinued and diuretic therapy and treatment with prednisolone was started with gradual dose reduction. This resulted in a rapid complete resolution of the symptoms. The next PET-CT in July 2023 continued to show CR (DS:3) without evidence of pneumonitis. Currently, therapy with MEPED has not been resumed. In conclusion, we demonstrate for the first time that MEPED therapy is highly effective in a patient with Hodgkin's disease who has been refractory to ICPi. Sustained CR was achieved over 11 months after initiation of MEPED therapy. Further studies on a larger patient cohort should be performed.